Antimicrobial Capacity and Surface Alterations Using Photodynamic Therapy and Light Activated Disinfection on Polymer-Infiltrated Ceramic Material Contaminated with Periodontal Bacteria - Elzahraa Eldwakhly; Selma Saadaldin; Alhanoof Aldegheishem; Marwa Salah Mostafa; Mai Soliman (MDPI AG, 2020)
This study determined the antimicrobial efficiency of light-activated disinfection (LAD) and photodynamic therapy (PDT) on polymer-infiltrated ceramic network (PICN) material contaminated with three periodontal bacteria and explored if PDT and LAD cause PICN surface alterations. Sixty PICN discs were contaminated with Tannerella forsythia, Porphyromonas gingivalis, and Treponema denticola and randomly divided into five groups (n = 12 samples/each) according to the treatment groups: Group PDT-PDT (630 ± 10 nm diode laser) with methylene blue; Group DL-808 nm diode laser in contact mode without photosensitizer; Group MB-methylene blue without light application; Group CHX-0.12% chlorhexidine digluconate solution and; Group NT-no treatment. Each disc was then placed in tubes containing phosphate buffered saline (PBS) and vortexed for 30 s to remove the remaining bacteria from the discs. A total of 10× serial dilutions were performed followed by plating of 30 μL of suspension on Brucella agar plates. The colony forming units (CFU) were calculated after 72 h. PICN discs with the attached biofilms were used for confocal microscopy investigation for live/dead bacterial viability. A random single sample from each group was selected to study the bacterial adherence and topographical alterations on PICN discs under scanning electron microscope (SEM). The PDT group showed higher reduction for each bacterial species and total counts of bacteria assessed followed by the DL group (p < 0.05). When compared with MB group, the two laser groups were significantly superior (p < 0.05). The MB group did not show significant differences for any bacteria when compared to NT. The bacteria with the CHX group and DL groups appeared dead with few areas of surviving green stained bacteria. The PDT group showed the highest dead cell count (p < 0.05). PDT and DL groups indicate no significant changes on the surface compared to the sterile PICN discs on visual assessment. Photodynamic therapy produced superior periodontal bacteria reduction over the surface of PICN surface. PDT group showed higher reduction for each bacterial species and total counts of bacteria assessed followed by the DL group. Both PDT and DL treatment strategies are effective without producing surface alterations on PICN.